UMPSA organises Road Safety Campaign ‘Pandu Cermat Sampai Selamat’ - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 4 April 2024 - A total of about 600 Universiti Malaysia Pahang Al-Sultan Abdullah students received benefits from the ‘Pandu Cermat Sampai Selamat’ Road Safety Campaign starting from 4 to 6 April 2024.